Perfil magazine, Costa Rican literature and the first novel about Yolanda Oreamuno (1984-2024) - Molina Jiménez, Iván (2025)
Created in 1984, the women’s magazine Perfil became a space of dispute between those who perpetuated traditional gender values and those who identified with feminist approaches. From its beginnings, Perfil began to publish original stories and novels, as well as book reviews and interviews with writers. This article offers an inventory of these texts, as well as the transcription of the first novel about the renowned Costa Rican author Yolanda Oreamuno, published in Perfil in 1987.